Microplastics: addressing ecological risk through lessons learned. (May 2015) - Syberg, Kristian; Khan, Farhan R.; Selck, Henriette; Palmqvist, Annemette; Banta, Gary T.; Daley, Jennifer; Sano, Larissa; Duhaime, Melissa B.
Abstract: Plastic litter is an environmental problem of great concern. Despite the magnitude of the plastic pollution in our water bodies, only limited scientific understanding is available about the risk to the environment, particularly for microplastics. The apparent magnitude of the problem calls for quickly developing sound scientific guidance on the ecological risks of microplastics. The authors suggest that future research into microplastics risks should be guided by lessons learned from the more advanced and better understood areas of (eco) toxicology of engineered nanoparticles and mixture toxicity. Relevant examples of advances in these two fields are provided to help accelerate the scientific learning curve within the relatively unexplored area of microplastics risk assessment. Finally, the authors advocate an expansion of the "vector effect" hypothesis with regard to microplastics risk to help focus research of microplastics environmental risk at different levels of biological and environmental organization. Environ Toxicol Chem 2015;34:945–953. © 2015 SETAC